Conclusion on the peer review of the pesticide risk assessment of the active substance pyraflufen‐ethyl. (4th February 2015) - ,; ,
Abstract: The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessments carried out by the competent authority of the rapporteur Member State the Netherlands, for the pesticide active substance pyraflufen‐ethyl are reported. The context of the peer review was that required by Commission Regulation (EU) No 1141/2010 as amended by Commission Implementing Regulation (EU) No 380/2013. The conclusions were reached on the basis of the evaluation of the representative uses of pyraflufen‐ethyl as a herbicide on potato and grape vines. The reliable endpoints concluded as being appropriate for use in regulatory risk assessment, derived from the available studies and literature in the dossier peer reviewed, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.